A rare presentation of silicone oil induced secondary glaucoma with 360 degree iris bombe formation - Kochar, Rashi; Ahuja, Nisha; Parmar, Hitendra; Katara, Pushkal (International Journal of Research in Medical Sciences, 2023)
A 53-year-old male presented to our centre complaining of sudden onset of headache and decreased vision in the right eye for 1 month. Patient had history of injury with an iron wire at the work place for which patient under went for right eye scleral tear repair with Pars Plana Vitrectomy. On examination, visual acuity was hand movements in right eye. Anterior segment examination of right eye revealed circumcorneal congestion, 360 degree of iridocorneal apposition, flat anterior chamber with iris bombe and pupillary membrane formation. Laser peripheral iridotomy was performed which led to the egress of silicone oil through the peripheral iridotomy into the anterior chamber, relieving the iridocorneal apposition. At subsequent follow up visit there was further reduction in iridocorneal apposition and iris bombe.